P234 Patient and fluid characteristics associated with non-draining malignant pleural effusion. (15th November 2017) - Mishra, EK; Clive, A; Davies, HE; Nunn, AJ; Miller, RF; Psallidas, I; Maskell, NA; Rahman, NM
Abstract : Introduction: TIME3, a randomised controlled trial of intrapleural urokinase versus placebo for patients with non-draining malignant pleural effusion (MPE), demonstrated that these patients appear to be a distinct subgroup of patients with a poor prognosis (median survival 58 days). The aim of this study was to identify patient and fluid characteristics associated with this subgroup, to enable further understanding of why patients with non-draining effusion may have poor prognosis. Methods: Baseline demographics and pleural fluid (PF) characteristics of patients enrolled in TIME3 were compared to patients enrolled in TIME2, 2 a randomised controlled trial of indwelling pleural catheter versus chest drain and pleurodesis for patients with recurrent MPE. Demographic characteristics compared were: age, sex, histological type of cancer and ECOG performance status (PS). Pleural fluid characteristics compared were: total protein, glucose, cytology (positive or negative), pH, lactate dehydrogenase (LDH) and presence of septations on ultrasound. These characteristics were compared using t test for linear variables and chi squared for categorical variables. Results: The median survival was 58 days (IQR 27–123) in TIME3 versus 187 days (IQR 48–358) in TIME2. Patients with non-draining effusions had a significantly higher PF LDH (mean 1900 (SD 3100) versus 660 (SD 840), p<0.001) and CRP (mean 117 (SD 80) versus 62 (SD 55), p<0.001). Patients in TIME3 were on average 4 years older (mean 71 years in TIME3 versus 67 in TIME2, p=0.01) and less likely to be cytology positive (24% versus 51%, p=0.021). Conclusion: Non draining MPEs have a higher LDH than those without. There was a large difference in mortality between groups, but despite this no identifiable differences in baseline ECOG, PS or tumour type, despite these variables being associated with a poor prognosis in unselected cohorts of patients with MPE. 1 We postulate that survival in MPE may be associated with septations and the intrapleural inflammatory milieu. Further study of the association between PF LDH, septations and survival is warranted. References: Clive, A. O. Predicting survival in malignant pleural effusion: Development and validation of the LENT prognostic score. Thorax2014;69(12):1098–104. Davies HE, M. E. TIME2 randomised controlled trial. Journal of the American Medical Association2012;2383–9.